THE VALIDITY OF TENSES IN TRANSLATION BETWEEN USING ONLINE AND MANUAL TRANSLATION IN ENGLISH STUDENTS 2017-B OF STKIP PGRI JOMBANG - Dina Cahya Restu Setya Putri (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2019)
Translation has always been the core of the controversy on whether it can be a valid and effective tool in foreign language learning. Translation is a language learning activity considered appropriate in the context of foreign language learning (Brown, 2002). The aim of the study is how to know most effective in translation, google translation or manual translation. The participant are 2017-B students (8 females and 2 males) learning grammar. Their background knowledge would help them to effectively acquire manual translation and based knowledge during online translation help their learning outcomes. The sig value is 0,006 < 0,05 it means that; Ho is rejected and Ha accepted. Which mean that there is significant different in student translate with manual translation and using online translation. So, the student has more easy understanding with the online translation. Based on the result of the table about the score with analyze using SPSS in T-Test student on average get better score in online translation. It means that error tenses or the validity tenses more accurate with online translation. Base on the result of this research we can see that online translation is more valid when translating, but manual translation can also produce better translated results if we add to our background knowledge we can see that still many student can not understand about the material in prepositional grammar.